Handbook of resilience in children of war - Ferrari, Michel; Fernando, Chandi (Springer New York, 2013)
Their frightened, angry faces are grim reminders of the reach of war. They are millions of children, orphaned, displaced, forced to flee-or to fight. And just as they have myriad possibilities for trauma, their lives also hold great potential for recovery. The Handbook of Resilience in Children of War explores these critical phenomena at the theoretical, research, and treatment levels, beginning with the psychosocial effects of exposure to war. Narratives of young people's lives in war zones as diverse as Afghanistan, Sri Lanka, Columbia, and Sudan reveal the complexities of their experiences and the meanings they attach to them, providing valuable keys to their rehabilitation. Other chapters identify strengths and limitations of current interventions, and of constructs of resilience as applied to youth affected by war. Throughout this cutting-edge volume, the emphasis is on improving the field through more relevant research and accurate, evidence-based interventions, in such areas as: An ecological resilience approach to promoting mental health in children of war. Child soldiers and the myth of the ticking time bomb. The Child Friendly Spaces postwar intervention program. The role of education for war-zone immigrant and refugee students. Political violence, identity, and adjustment in children. The Handbook of Resilience in Children of War is essential reading for researchers, scientist-practitioners, and graduate students in diverse fields including clinical child, school, and developmental psychology; child and adolescent psychiatry; social work; counseling; education; and allied medical and public health disciplines.